2019
DOI: 10.1182/blood-2018-09-875732
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b trial of an ibrutinib-based combination therapy in recurrent/refractory CNS lymphoma

Abstract: Ibrutinib is a first-in-class inhibitor of Bruton tyrosine kinase (BTK) and has shown single-agent activity in recurrent/refractory central nervous system (CNS) lymphoma. Clinical responses are often transient or incomplete, suggesting a need for a combination therapy approach. We conducted a phase 1b clinical trial to explore the sequential combination of ibrutinib (560 or 840 mg daily dosing) with high-dose methotrexate (HD-MTX) and rituximab in patients with CNS lymphoma (CNSL). HD-MTX was given at 3.5 g/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(206 citation statements)
references
References 22 publications
6
196
2
2
Order By: Relevance
“…Of further interest, ibrutinib has been reported to cross the blood‐brain barrier and has recently shown efficacy in CNS lymphomas and in MCL involving the CNS . These results have potential to impact future therapies for high‐risk MCL patients who have CNS involvement or at high risk of CNS involvement.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 98%
“…Of further interest, ibrutinib has been reported to cross the blood‐brain barrier and has recently shown efficacy in CNS lymphomas and in MCL involving the CNS . These results have potential to impact future therapies for high‐risk MCL patients who have CNS involvement or at high risk of CNS involvement.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 98%
“…Adding BTK inhibitor to the standard DLBCL chemoimmunotherapy R-CHOP regimen in non-GCB-DLBCL did not improve survival 202 but other combinations might prove to be more beneficial. BTK inhibition has proven quite successful when used as a single agent in PCNSL (primary central nervous system DLBCL) and secondary CNSL, [203][204][205] with clinical response seen in 78% of CNS lymphoma patients in a phase II study. 204 An Ibrutinib/Methotrexate/ Rituximab combination has shown manageable toxicity and promising results in relapsed/refractory CNS lymphomas with 80% clinical response rate in a phase Ib trial.…”
Section: Therapeutic Targeting Of Aberrant Signal Transductionmentioning
confidence: 99%
“…BTK inhibition has proven quite successful when used as a single agent in PCNSL (primary central nervous system DLBCL) and secondary CNSL, [203][204][205] with clinical response seen in 78% of CNS lymphoma patients in a phase II study. 204 An Ibrutinib/Methotrexate/ Rituximab combination has shown manageable toxicity and promising results in relapsed/refractory CNS lymphomas with 80% clinical response rate in a phase Ib trial. 204 Targeting further downstream components of the BCR pathway is desirable in order to bypass BTK inhibitor resistance conferred by mutations of genes such as PLCγ, CARD11, and BCL10.…”
Section: Therapeutic Targeting Of Aberrant Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the sequential combination of ibrutinib with high-dose methotrexate and rituximab was studied in patients with primary central nervous system lymphoma (PCNSL) (NCT02315326). 203 Acalabrutinib (ACP-196) is a BTK inhibitor that has been proven to have a more enhanced efficacy than ibrutinib in canine studies. 204 A phase 2 study (NCT02213926) reported an ORR of 81% (CR 40%) in relapsed or refractory MCL.…”
Section: Bcr-btkmentioning
confidence: 99%